PENGARUH PROFITABILITAS, LEVERAGE DAN PERTUMBUHAN PENJUALAN TERHADAP PENGHINDARAN PAJAK - Hidayat, Wastam Wahyu (Economic Faculty, Attahiriyah Islamic University, 2018)
The research aims to analyze the effect of profitability, leverage, and sales growth on tax avoidance. Data were collected from 25 companies from manufacture listed in Indonesia Stock Exchange (IDX) in 2011 to 2014. The analysis method of this research used multiple regression. The results showed that profitability and sales growth had a negative and significant effect on tax avoidance (p-value <0.05), while leverage was not successfully supported. Overall, the model's ability to explain tax avoidance is 29.60%. Discussions and limitations are discussed in the paper. Keywords: profitability, leverage, sales growth, tax avoidance